METHODOLOGICAL BASES FOR ASSESSING THE EFFICIENCY OF THE MANAGEMENT OF THE TEXTILE INDUSTRY ENTERPRISE (ResearchJet Journal of Analysis and Inventions, 2022)
This article discusses the development, implementation and practical application of models and methods for assessing the management of activities and development, which are an important condition for improving the financial and economic condition of the textile industry enterprise. A lot of attention is paid to the theory and practice of enterprise management in the textile industry. The issue of effective management of the textile industry enterprise is covered in modern literature.